Evaluation Of Village Fund Allocation Contribution (ADD) On Village Economic Development And Rural Business Growth In Indragiri Hilir Regency - Sutikno, Sutikno; Suliswanto, Muhammad Sri Wahyudi (Badan kebijakan Fiskal, 2018)
This study aims (a) to analyze the role of ADD as a budget stimulant to encourage the growth of the real sector business in the village. (b) to investigate the role of ADD on the development of village potential. The analytical instrument applied was Structural Equation Modeling (SEM) or also called Linear Structural Equation (LISREL). The results of this study are: (a) the variable of village potential / featured development following ADD program is the condition of infrastructure (X4) with a correlation value of 0.81. (b) variable of rural enterprises growth financed (impact) by ADD is the infrastructure condition (X4) with a correlation value of 0.33.